PENGARUH PENGALAMAN KERJA DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP LOYALITAS KARYAWAN - Fajariani, Ni Putu Eka; Surya, I.B.Ketut (E-Jurnal Manajemen, 2015)
Employee loyalty is very important for the survival and growth of productivity. Direction of this study to examine the work experience and transformational leadership on loyalty. This study uses saturated sample of 52 employees with multiple linear regression analysis techniques. This study shows the results of that work experience and transformational leadership and significant positive effect simultaneously and partially on employee loyalty. Based on the research results, the expected leader can improve the training programs, provide motivation in the form of incentives, rewards and holiday allowances that can increase employee loyalty.
Keywords: work experience, transformational leadership, employee loyalty.